PEER GROUP COUNSELING IN IMPROVING PROSIAL BEHAVIOR OF ADOLESCENT IN SURABAYA - Yuni Sufyanti Arief; Ilya Krisnana; Iqlima Dwi Kurnia; Praba Diyan Rachmawati (Jurnal Pengabdian Masyarakat Dalam Kesehatan, 2021)
Introduction: Social problems that occur in adolescent students lead to anti-social behavior. Antisocial behavior is a disorder of adjustment to the social environment caused by weak self-control. The purpose of this community service is to provide knowledge and abilities to junior high school students as peer counselors so that they can develop adolescent prosocial behavior and can prevent antisocial behavior.Methods: The method used in this community service activity is training with the method of lectures and discussions on peer counseling, prosocial behavior in adolescents, and skills as a peer counselor. A total of 40 people consisting of selected students, counseling teachers, and person in charge of students participated in this activity and also carried out an evaluation of adolescent prosocial behavior through the pretest and posttest.Results: The results obtained through this activity are that there is an increase in the knowledge and attitudes of adolescents in developing prosocial behavior. This is because the method of lectures, discussions, through training modules can provide a clear technical picture so that participants know and can practice their abilities as peer counselors in improving prosocial behavior of junior high school adolescents.Conclusion: It is hoped that the next community service activity can achieve a wider target and a diverse community.